Mapping the Intellectual Landscape of Prophetic Literature: A Comprehensive Bibliometric Analysis - Putra, Candra Rahma Wijaya; Sunaryo, Hari; Hiasa, Fina (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
Prophetic literature is literature with a pattern of transcendence. The history of literature in Indonesia has many prophetic literary works. Prophetic literature has the purpose of introducing prophetic values. The purpose of this research is to make a research mapping of prophetic literature globally. The goal is to map developments, trends, and research opportunities about prophetic literature. A bibliometric analysis was conducted to examine prophetic literature publications from the Scopus database. Using the search terms